Interstitial oxygen's influence on the corrosion behavior of Ti-9Mo alloys - Nogueira, R. a. [UNESP]; Pinto, L. m. c. [UNESP]; Ângelo, A. c. d. [UNESP]; Claro, A. p. r. a. [UNESP]; Grandini, Carlos Roberto [UNESP] (ABM, ABC, ABPol, 2013)
Titanium and its alloys have been used in biomedical applications because of their satisfactory mechanical properties, biocompatibility and corrosion resistance. Their high corrosion resistance has been attributed to the formation of a thermodynamically stable titanium oxide layer on the surface of these materials. In the present work, the corrosion behavior of Ti-9Mo (wt %) alloy, doped with oxygen, was evaluated in a phosphate buffered saline (PBS) solution. The results showed a small decrease in the corrosion potential and a reduction in the corrosion rate with the oxygen doping, indicating a higher corrosion resistance is desirable for biomedical applications.
Keywords: Ti alloys; corrosion; potentiostatic method; repassivation